Assistive technology and passengers with special assistance needs in air transport: contributions to cabin design - Carina Campese; Talita Naiara Rossi da Silva; Larissa Lunardon Gomes da Silva; Julia Pierre Figueiredo; Nilton Luiz Menegon (Production)
Abstract There has been significant growth in air transport worldwide, as well as in Brazil. However, studies have emphasized that disabled, obese, and elderly passengers face difficulties when using this means of transport. Among these difficulties, issues related to passengers’ own assistive devices, including damage, loss, or the impossibility of using during the entire flight, stand out. Therefore, the present study aims to understand the trends in assistive technology focusing on cabin design. This research is based upon literature review, interviews with manufacturers and research centers, visits to specialized trade fairs, and patent search. The results revealed a great diversity of assistive products, its trends, and an increase in their use, which affect aircraft cabin design, especially in terms of space, access, and stowage of these devices.